2008
DOI: 10.1002/eat.20632
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward weight gain during pregnancy: Results from the Norwegian mother and child cohort study (MoBa)

Abstract: Objective-To explore attitudes toward weight gain during pregnancy in women with and without eating disorders and across eating disorder subtypes, and to examine associations among weight-gain attitudes and actual gestational weight gain, infant birth weight, and infant size-forgestational-age. (35,929) enrolled in the prospective population-based Norwegian Mother and Child Cohort Study (MoBa) provided information at approximately week 18 of gestation regarding eating disorders and weight gain attitudes. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
9

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 48 publications
1
22
0
9
Order By: Relevance
“…In particular, a large study which assessed symptoms in AN in detail found that behaviour tends to change but cognitive/emotional symptoms remain high . Some healthy pregnant women also have high levels of concern about their weight and shape (Swann et al, 2009), and these also tend to be stable during pregnancy (Duncombe et al, 2008). This parallels the stability in our sample, although concerns are clearly greater in those with AN .…”
Section: Theme 1: Effortful Resistance Of Ansupporting
confidence: 74%
See 1 more Smart Citation
“…In particular, a large study which assessed symptoms in AN in detail found that behaviour tends to change but cognitive/emotional symptoms remain high . Some healthy pregnant women also have high levels of concern about their weight and shape (Swann et al, 2009), and these also tend to be stable during pregnancy (Duncombe et al, 2008). This parallels the stability in our sample, although concerns are clearly greater in those with AN .…”
Section: Theme 1: Effortful Resistance Of Ansupporting
confidence: 74%
“…Historically, such changes were considered unimportant (Earle, 2003). Although little researched, work now suggests many pregnant women are very worried about their weight and shape (Swann et al, 2009). Although findings are inconsistent, as pre-existing concerns may alter in various ways, it appears that worries about weight and shape rarely disappear if previously present (Duncombe, Wertheim, Skouteris, Paxton & Kelly, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…11,41 Moreover, perinatal complications associated with a lifetime ED diagnosis include an increased risk for hyperemesis, 13,42 smoking during pregnancy, 43 lower birth weight, and birth defects such as cleft palate and neural tube defects, microcephaly, preterm delivery, and cesarean delivery. 12,16,40,[44][45][46][47] Trauma and abuse history in eating disorders and perinatal depression Women with lifetime histories of EDs are also more likely to report a history of childhood sexual abuse and physical abuse compared with women with no ED history.…”
mentioning
confidence: 99%
“…Embora não seja formalmente reconhecida a ocorrência de TA na gestação, sugere-se que seja menos comum do que na população em geral 9 . Alguns estudos exploraram a presença desses transtornos nessa fase da vida, bem como a preocupação com o ganho de peso na gravidez [10][11][12][13] . A compulsão alimentar é o comportamento inadequado mais relatado durante o período gestacional, e geralmente é acompanhado de ganho de peso excessivo.…”
Section: Introductionunclassified
“…Gestantes com TCA têm bebês com maior peso, grandes para a idade gestacional, e apresentam maior risco de parto cirúrgico -desfecho indiretamente influenciado pelo ganho excessivo de peso materno 11 . Tal ganho associado ao TCA durante a gestação representa maior risco de retenção de peso no pós-parto, obesidade, problemas com a imagem corporal e comprometimento da saúde da mãe e da criança 13 . Devido ao fato de que muitas mulheres durante a gestação tentam controlar o peso com a adoção de méto-dos inadequados, é fundamental diagnosticar um TA na gravidez.…”
Section: Introductionunclassified